Practical Model Intelligence Computer Assisted Instruction project-based learning-oriented High Order Thinking Skill - et. al., Tongam E Panggabean, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In order to adapt to the challenges of the 21st century, efforts to improve the quality of education must be made through the provision of communication skills, teamwork skills, critical thinking, and problem-solving skills as well as innovative orientation and creativity for students. In this connection, of course, learning in the 21st century has made ICT an important part of the learning process through the growth of constructivism and constructivism. For this reason, this study was conducted to measure the practicality of the Intelligence Computer Assisted Instruction model of project-based learning-oriented at Higher Level Thinking Skills for lecturers and students, so that practical models can be used in learning. This study uses the Borg and Gall model steps by assessing the practicality of a model that has previously been declared valid. The subject of practicality testing is a lecturer who teaches an expert system course, a trial for students who take an expert system course. The instrument used was a practicality questionnaire. The data analysis technique used the Akien test to see the practicality of the model being developed. The results of the project-based learning model of Intelligence Computer Assisted Instruction practicum oriented at Higher Level Thinking Skills for lecturers and students which contain model books, lecturer manuals, and teaching modules are classified as very practical. From these results, it is stated that the project-based Intelligence Computer Assisted Instruction learning model that is oriented towards High-Level Thinking Skills is stated to have a practicality that is feasible to use